Reading in print and hypertext environments: A comparative study of good L2 readers comprehensive strategies - Bolaños, Eduardo A. (Animo Repository, 2009)
The main concern of this descriptive study is to investigate the comprehension strategies good L2 readers employ when they read expository texts in print and hypertext environments. Of corollary interest to the aforesaid primary concern is a three-fold purpose: 1) to determine the readers level of comprehension in the two environments, 2) to find out if there is a difference in their comprehension, and 3) to examine if there is a relationship or association that exists among the important constructs in the study such as reading environments, reading strategies, and comprehension. In the study, sixteen (16) female college freshmen participants were randomly and evenly distributed into two groups of equally good readers. They were then asked to concurrently read and think aloud that revealed their individual comprehension processing strategies. After reading each of the three texts, the participants were asked to summarize each text and then answer two questions as measures of their comprehension. Interpretations and analyses of the protocols and comprehension outputs were guided by Glasers (1992) and Glaser and Strausss (1967) grounded theory. The theoretical underpinnings cited in the study, most notably, the view on reading as an interactive, constructive, meaningmaking, and problem-solving process (Alexander & Jetton, 2000 NICHD, 2000 RRSG, 2002 Spivey, 1987, as cited in Coiro & Dobler, 2007) which is applicable to the two reading environments (print and hypertext) in the study was utilized to help elucidate the data. Results of the study indicate that, in general, good L2 readers of expository texts employ a multistrategic approach to reading (Jimenez, Garcia, & Pearson, 1995, p. 80) which means Reading in Print and Hypertext ! # ! ! that they use a wide repertoire of coordinated strategies when they process texts. These strategies are almost the same in both environments. The findings also reveal that, overall, the level of comprehension of the participants is the same regardless of environments, though there is indication that print readers have a slight advantage over the hypertext group. As regards difference in comprehension, on the whole, results indicate that the difference is not significant, suggesting that reading environments may not affect or influence comprehension, its level, and quality, significantly. Lastly, results likewise reveal that there is a significant association/relationship between reading environments and reading strategies, implying that an environment may trigger usage of a particular strategy or vice versa. The same finding is true of reading strategy and level of comprehension, which means that the more frequently and/or effectively the strategies are used, the better and/or more effective the comprehension becomes. On the other hand, results of reading environments and level of comprehension reveal no association/relationship between the two constructs. This may mean that reading environment and level of comprehension are independent of each other that, regardless of environment, comprehension level of good L2 readers may remain the same. In the light of the above findings, it is recommended that strategy-anchored reading programs that cut across curriculum and academic levels be developed, assessed, and adopted to strengthen meaning making of the text among readers. Teacher strategy training is also seen as a viable means to improve comprehension instruction and comprehension among readers of texts in various forms.